Pengaruh Perbedaan Ukuran dan Massa Adsorben Pelepah Sawit Teraktivasi dalam Pemurnian Minyak Jelantah Menggunakan Metode Shaker - Fithry, Dwi Annisa; Bode Haryanto; Naia Salsa Billah; Astrina Hutabarat; Hidayat Prayogo (SURYA TEKNIKA, 2023)
Used oil more commonly referred to as used cooking oil is household waste that contains carcinogenic compounds which are very dangerous if consumed by the human, so that it does not become waste in the community can be used as raw material for making biodiesel. Used cooking oil processing can be done with the use of adsorbents so that used cooking oil becomes clear and its quality can be maintained. Palm Oil has the potential to be used as carbon which functions as an Adsorbent in the refining of used cooking oil. In this study, palm fronds were carbonized using pyrolysis with a temperature of 3500C then mashed and sifted with mesh sizes of 50, 70, and 100 mesh. Followed by the activation process using 0.1 M sulfuric acid solution (H2SO4) for 3 hours and then dried using an oven. The results of the study showed that the best turbidity was an adsorbent measuring 100 mesh with a mass of 4.5 grams, the final turbidity obtained with a value of 15.9 NTU with a total turbidity reduction of 108.6 NTU.